Anti-aging SBS modified asphalt coating material, waterproof coiled material and preparation method
By using raw materials such as Kujiao 70# asphalt and anti-aging high-grade waterproof asphalt, combined with SBS, waste glue powder and sesapite powder, aging-resistant SBS modified asphalt coating material and waterproof coil material are prepared, which solves the problems of environmental pollution and anti-aging performance in the existing technology, and achieves efficient and environmentally friendly waterproof performance and long life.
Patent Information
- Application Number
- CN202311432058.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-10-31
AI Technical Summary
The existing SBS modified asphalt waterproof coils need to be added to softened oil during the production process, resulting in reduced environmental pollution and anti-aging performance. The waste rubber powder releases harmful flue gas during the high-temperature production process, endangering human health and the environment.
Using 70# asphalt and high-grade anti-aging waterproof asphalt as raw materials, SBS, waste glue powder and sesapite powder are added to form aging-resistant SBS modified asphalt coating material and waterproof roll material through specific formulas and preparation methods.
This technical method improves the anti-aging and waterproof properties of waterproof coils, extends the service life, avoids environmental pollution and health hazards, and reduces production costs.
Smart Images

Figure BDA0004523940280000091 
Figure BDA0004523940280000092 
Figure BDA0004523940280000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building waterproof engineering, and particularly relates to an aging-resistant SBS modified asphalt coating material and a waterproof coiled material, and further discloses a preparation method thereof. Background Art
[0002] Modified asphalt waterproofing membranes play a vital role in building waterproofing projects. They are widely used for waterproofing roofs, underground structures, and other specialized structures, making them a widely used and widely available waterproofing material. Currently, elastomer (SBS) modified asphalt waterproofing membranes remain the mainstream product in the domestic market, particularly for use on exposed roofs, where their superior high-temperature resistance is difficult to replace with other materials.
[0003] The existing commercially available elastomer (SBS) modified asphalt requires the addition of softening oil during the production process. Its preparation process is relatively complicated. In addition, due to the volatile organic matter contained in the softening oil, the light component is easily volatile during the production process of the polymer modified asphalt, which not only pollutes the environment and affects the anti-aging performance of the waterproof material, but also reduces the life of the waterproof membrane, causing unnecessary economic losses. Moreover, waste rubber powder is usually required to be added during the production process of modified asphalt. Although waste rubber powder modified asphalt can consume a large amount of discarded tires, the waste rubber will release a large amount of harmful smoke during the high-temperature production process, which not only endangers human health, but also poses a great challenge to the environment. In particular, waterproof membranes are very prone to aging when exposed for a long time, resulting in a large number of cracks or fissures on the surface of the waterproof layer, affecting the waterproof function and the service life of the material. Summary of the Invention
[0004] Therefore, the technical problem to be solved by the present invention is to provide an aging-resistant SBS modified asphalt coating material, which has the advantages of high strength, environmental protection, good water resistance, and good high and low temperature performance and aging resistance, effectively extending the service life of the modified asphalt coating material;
[0005] The second technical problem to be solved by the present invention is to provide an aging-resistant SBS modified asphalt waterproof membrane;
[0006] The third technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned aging-resistant SBS modified asphalt coating material and waterproof membrane.
[0007] To solve the above technical problems, the present invention discloses an aging-resistant SBS modified asphalt coating material, which comprises the following raw materials in parts by weight: 40-50 parts by weight of 70# asphalt, 50-60 parts by weight of high-grade waterproof asphalt, 8-12 parts by weight of SBS, 10-20 parts by weight of waste rubber powder, and 10-15 parts by weight of sepiolite powder;
[0008] The high-grade waterproof asphalt includes the following raw materials: base asphalt, catalytic slurry, furfural extracted oil, conversion agent, filler, adsorbent;
[0009] The mass ratio of the matrix asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler and adsorbent is 70-80:6-10:10-18:0.1-0.25:1-3:0.03-0.05.
[0010] Specifically, the aging-resistant SBS modified asphalt coating material:
[0011] The melt index of the SBS is 0.03-0.10 g / min; and / or,
[0012] The particle size of the waste rubber powder is 60-80 mesh; and / or,
[0013] The particle size of the sepiolite powder is 80-100 meshes.
[0014] Specifically, in the aging-resistant SBS modified asphalt coating material, the high-grade waterproof asphalt, the furfural extracted oil includes one or a mixture of three-line furfural extracted oil and four-line furfural extracted oil;
[0015] Preferably, the aromatic content in the furfural extracted oil is ≥40%.
[0016] Specifically, in the aging-resistant SBS modified asphalt coating material and the high-grade waterproof asphalt, the adsorbent includes bamboo nanofiber aerogel;
[0017] Preferably, the preparation method of the bamboo wood nanofiber aerogel comprises the steps of taking bamboo wood cellulose nanofibers and placing them in water and ethanol solutions in sequence for immersion, and the step of pressurizing and heating the nanofibers;
[0018] Preferably, the impregnation step comprises the steps of adding water to the bamboo lignocellulose nanofibers and impregnating them for 20-30 hours, and then taking out the nanofibers and adding ethanol solution to continue impregnating them for 20-30 hours;
[0019] Preferably, the impregnation step comprises the steps of adding water to the bamboo lignocellulose nanofibers and impregnating them for 24 hours, and then taking out the nanofibers and adding ethanol solution to continue impregnating them for 24 hours;
[0020] Preferably, the pressurized heat treatment step is performed for 6-10 hours, preferably 8 hours.
[0021] Specifically, in the aging-resistant SBS modified asphalt coating material and the high-grade waterproof asphalt, the filler includes activated palygorskite;
[0022] Preferably, the method for preparing the activated palygorskite comprises the steps of adding the palygorskite to dilute hydrochloric acid and mixing, and treating the palygorskite at 50-80° C.; preferably, the treatment temperature is 60° C.;
[0023] Preferably, the mass concentration of the dilute hydrochloric acid is 1%-2%;
[0024] Preferably, the mass ratio of the palygorskite to the dilute hydrochloric acid is 1:2-4 g / mL; the preferred mass ratio is 1:3 g / mL;
[0025] Preferably, the treatment time is 40-80 min;
[0026] Preferably, the method further comprises the steps of washing and drying the treated activated palygorskite.
[0027] Specifically, the aging-resistant SBS modified asphalt coating material and the high-grade waterproof asphalt include:
[0028] The matrix asphalt includes heavy traffic 70# asphalt; and / or,
[0029] The aromatic content of the catalytic cracking slurry is 40%-48%; and / or,
[0030] The conversion agent includes silicotungstic acid.
[0031] The present invention also discloses a method for preparing the aging-resistant SBS modified asphalt coating, comprising the steps of mixing selected amounts of the 70# asphalt, high-grade waterproof asphalt, SBS, waste rubber powder and sepiolite powder;
[0032] Preferably, the temperature of the mixing step is 170-180°C;
[0033] Preferably, the method further comprises the step of performing high-speed shearing at a rotation speed of 3000-3500 r / min for 1-1.5 hours during the mixing process;
[0034] Preferably, the method further comprises the step of performing high-speed shearing at a rotation speed of 3200 r / min for 1.2 h during the mixing process.
[0035] Specifically, the method for preparing the aging-resistant SBS modified asphalt coating further comprises the step of preparing the high-grade waterproof asphalt, namely, the step of mixing selected amounts of the base asphalt, catalytic slurry, furfural extracted oil, conversion agent, absorbent and filler;
[0036] Preferably, the temperature of the mixing step is 120°C-130°C, preferably the mixing temperature is 125°C.
[0037] Specifically, the method for preparing the high-grade waterproof asphalt comprises the following steps:
[0038] (1) heating a selected amount of the matrix asphalt to 120° C.-130° C.;
[0039] (2) continuing to add a selected amount of the catalytic oil slurry and furfural extracted oil, and performing high-speed shearing at a speed of 1000-1500 r / min for 30-40 min; preferably, performing high-speed shearing at a speed of 1200 r / min for 35 min;
[0040] (3) continuing to add the selected amount of the conversion agent and absorbent, and continuing shearing for 20-40 minutes, and then continuing shearing under ultrasonic conditions for 0.5-1 hour;
[0041] (4) Continue to add the selected amount of the filler and continue shearing for 20-40 minutes.
[0042] Specifically, in the method for preparing high-grade waterproof asphalt, in the step (3), the power of the ultrasonic step is 4-8W, preferably 6W, and the ultrasonic time is 0.5-1h.
[0043] The present invention also discloses an aging-resistant waterproof coiled material, comprising a polyester felt reinforcement, wherein a modified asphalt rubber layer and a polyethylene film are sequentially arranged on the upper and lower surfaces of the reinforcement;
[0044] The modified asphalt rubber layer is formed by the aging-resistant SBS modified asphalt coating material.
[0045] The present invention also discloses a method for preparing the aging-resistant waterproof coiled material, comprising the steps of coating the aging-resistant SBS modified asphalt coating material on the upper and lower surfaces of the polyester felt reinforcement respectively, and then covering them with the polyethylene film in turn.
[0046] The aging-resistant SBS modified asphalt coating and waterproofing membrane described in this invention utilizes heavy-duty 70# asphalt and aging-resistant high-grade waterproof asphalt as raw materials, along with SBS, waste rubber powder, and sepiolite powder. The synergistic effects of these components not only improve the material's aging resistance and waterproofing properties, but also effectively extend its service life. The aging-resistant SBS modified asphalt coating and waterproofing membrane described in this invention eliminate the need for softening oil to produce the waterproofing membrane coating, overcoming the complex process associated with traditional preparation methods. The unique structure of sepiolite powder reduces the membrane's surface temperature under high-temperature conditions, extending its service life. Furthermore, the use of waste rubber powder as a raw material not only rationally utilizes waste resources, significantly reducing production costs, but also increases the product's added value.
[0047] The anti-aging high-grade waterproof asphalt described in the present invention uses heavy traffic asphalt, slurry oil and furfural extracted oil as basic raw materials. By adding a selected conversion agent, adsorbent and filler raw material system, the volatilization of light components when the asphalt is heated can be greatly reduced. The various components work together to improve the anti-aging performance of the waterproof material, and a high-grade waterproof asphalt with better anti-aging performance is prepared.
[0048] The anti-aging high-grade waterproof asphalt of the present invention is prepared using catalytic cracking slurry oil and furfural extracted oil as raw materials. Since the catalytic cracking slurry oil and furfural extracted oil contain more saturated components and aromatic components, they are beneficial to the swelling of SBS during the preparation of the coiled material.
[0049] The anti-aging high-grade waterproof asphalt of the present invention is prepared by adding silicotungstic acid as a conversion agent. The presence of silicotungstic acid converts aromatic components into high-molecular-weight substances during heating, thereby reducing the volatilization of harmful substances and protecting the environment.
[0050] The aging-resistant, high-grade waterproof asphalt described in this invention uses palygorskite as a filler. A large number of palygorskite fibers, a natural mineral microfiber, form a reinforcing network that intertwines with the spatial network of SBS. This reduces the volatilization of low-molecular-weight saturated components in the asphalt and improves the asphalt's aging resistance. Furthermore, palygorskite's large specific surface area and unique layered chain structure create a large surface contact area with the asphalt, improving the asphalt's high- and low-temperature performance. Furthermore, after acidification, palygorskite can coat light components, reducing their volatilization, protecting the environment while improving the asphalt's low-temperature performance.
[0051] The anti-aging high-grade waterproof asphalt described in the present invention uses bamboo wood nanofiber aerogel as an adsorbent. The aerogel reacts during the preparation process, giving it a special fiber frame structure, which can adsorb organic light components that volatilize during the preparation process, reducing the volatilization of light components, protecting the environment, and improving the anti-aging performance of the waterproof membrane. It also improves the low-temperature performance of the membrane and improves the anti-aging performance.
[0052] The preparation method of the anti-aging high-grade waterproof asphalt described in the present invention adopts an ultrasonic treatment method during the mixing process, which improves the dispersibility of the absorbent and the converter, and the performance of the prepared high-grade waterproof asphalt is improved. It has the advantage of a simple and easy manufacturing process. Not only does the product have excellent anti-aging performance, but it also shortens the process flow for waterproof membrane manufacturers and greatly improves economic feasibility. It can be widely used in the production of elastomer / plastomer modified asphalt, self-adhesive polymer modified asphalt, pre-paved / wet-paved and modified asphalt waterproof membranes for roads and bridges.
[0053] The aging-resistant SBS modified asphalt coating and waterproof membrane of the present invention have various raw material components that work together. The SBS modified asphalt coating prepared by the present invention not only has a simple manufacturing process, excellent aging resistance, and is environmentally friendly, but also shortens the process flow for waterproof membrane manufacturers, making it economically feasible. The coating is suitable for waterproofing and anti-seepage in industrial and civil building roofs, walls, kitchens and bathrooms, basements, swimming pools, as well as roads, bridges, subways, reservoirs and other projects, and is also suitable for anti-corrosion protection of metal containers and pipelines. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention.
[0055] In the following preparation example of the present invention, the filler is activated palygorskite, and the preparation method of the activated palygorskite comprises: mixing palygorskite with 2% hydrochloric acid by mass at a material-liquid ratio of 1:3, treating at 60° C. for 60 minutes, washing with water, and drying to obtain the activated palygorskite.
[0056] In the following preparation example of the present invention, the adsorbent is bamboo wood nanofiber aerogel, and the preparation method of the bamboo wood nanofiber aerogel includes: soaking bamboo wood cellulose nanofibers in water for 24 hours, then taking out the bamboo wood nanofibers and continuing to soak them in an ethanol solution for 24 hours. After taking them out, heating the nanofibers in a pressurized oven for 8 hours to obtain the desired bamboo wood nanofiber aerogel.
[0057] In the following preparation examples, comparative preparation examples, embodiments and comparative examples of the present invention, the properties and parameters of the same raw material components are the same.
[0058] Preparation Example 1
[0059] Heat 70 parts of heavy-crosslinked 70# asphalt to 125°C, add 6 parts of catalytic oil slurry and 10 parts of furfural-reduced oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, and add 0.1 parts of silicotungstic acid and 0.03 parts of bamboo wood nanofiber aerogel, continue to shear for 30 minutes, and then continue to shear under ultrasonic conditions (power 6W) for 0.5 hours, continue to maintain the temperature, add 1 part of activated palygorskite and continue to shear for 30 minutes.
[0060] Preparation Example 2
[0061] Heat 75 parts of heavy-duty 70# asphalt to 125°C, add 8 parts of catalytic oil slurry and 14 parts of furfural-reduced oil, mix, and perform high-speed shearing at a speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, and add 0.15 parts of silicotungstic acid and 0.04 parts of bamboo wood nanofiber aerogel, mix, and continue shearing for 30 minutes, then continue shearing under ultrasonic conditions (power 6W) for 0.5 hours, continue to maintain the temperature, add 2 parts of activated palygorskite and continue shearing for 30 minutes.
[0062] Preparation Example 3
[0063] 80 parts of heavy-duty 70# asphalt are heated to 125°C, 10 parts of catalytic oil slurry and 18 parts of furfural-reduced oil are added and mixed, and high-speed shearing is performed at a speed of 1200r / min for 35 minutes; the temperature is continued to be maintained at 125°C, and 0.25 parts of silicotungstic acid and 0.05 parts of bamboo nanofiber aerogel are added and mixed, and the shearing treatment is continued for 30 minutes, and then the shearing is continued for 0.5 hours under ultrasonic conditions (power 6W), and 3 parts of activated palygorskite are added and shearing is continued for 30 minutes while maintaining the temperature.
[0064] Comparative Preparation Example 1
[0065] Heat 80 parts of heavy-crosslinked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural-reduced oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and shear for 30 minutes, then continue to shear under ultrasonic conditions (power 6W) for 0.5h, and finally add 3 parts of activated palygorskite at the same temperature and continue to shear for 30 minutes.
[0066] Comparative Preparation Example 2
[0067] Heat 80 parts of heavy-crosslinked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural-reduced oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, and then continue shearing for 0.5h under ultrasonic conditions (6W).
[0068] Comparative Preparation Example 3
[0069] Heat 80 parts of heavy-crosslinked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural-reduced oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, then continue to shear for 0.5 hours under ultrasonic conditions (6W), and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes.
[0070] Comparative Preparation Example 4
[0071] Heat 80 parts of heavy cross-linked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, mix, high-speed shear at a speed of 1200r / min for 35 minutes, and then continue shearing under ultrasonic (6W) conditions for 0.5h to obtain the product.
[0072] Comparative Preparation Example 5
[0073] Heat 80 parts of heavy-duty 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural-reduced oil, mix, and high-speed shear for 35 minutes at a speed of 1200r / min; continue to maintain the temperature at 125°C, add 0.25 parts of silicotungstic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, and finally add 3 parts of activated palygorskite at the same temperature and shear for 30 minutes to obtain the product.
[0074] Comparative Preparation Example 6
[0075] Heat 80 parts of heavy-crosslinked 70# asphalt to 125°C, add 10 parts of catalytic oil slurry and 18 parts of furfural extraction oil, and mix them at a high speed of 1200r / min for 35 minutes; continue to maintain the temperature at 125°C, add 0.25 parts of phosphomolybdic acid and 0.05 parts of bamboo wood nanofiber aerogel and shear for 30 minutes, then continue to shear for 0.5 hours under ultrasonic (6W) conditions, and finally add 3 parts of activated palygorskite at this temperature and shear for 30 minutes to obtain the product.
[0076] The properties of the high-grade waterproof asphalt prepared in the above Preparation Examples 1-3 were measured and shown in Table 1 below.
[0077] Table 1 Properties of high-grade waterproof asphalt in Preparation Examples 1-3
[0078]
[0079] The properties of the high-grade waterproof asphalt prepared in the above comparative preparation examples 1-6 were measured and shown in Table 2 below.
[0080] Table 2 Comparative properties of high-grade waterproof asphalt in Preparation Examples 1-6
[0081]
[0082] It can be seen from the data in Tables 1 and 2 above that the high-grade waterproof asphalt material prepared using the raw material system of the present invention has good application performance. In addition, the softening point increment of the prepared high-grade waterproof asphalt before and after aging is small, and the evaporation loss is small, indicating that the high-grade waterproof asphalt prepared using the present invention has good anti-aging performance.
[0083] In the following examples of the present invention, the desired asphalt coating material is prepared based on the anti-aging high-grade waterproof asphalt prepared in the aforementioned Preparation Example 3 as a raw material.
[0084] Example 1
[0085] First, mix 40 parts of 70# asphalt and 50 parts of high-grade waterproof asphalt (Preparation Example 3), and heat it to 175°C. Then add 8 parts of SBS and shear it at a speed of 3200r / min for 1.2h. Then add 10 parts of waste rubber powder and 10 parts of sepiolite powder and mix them. Continue shearing at this temperature and speed for 1h to obtain the modified asphalt coating.
[0086] The polyester felt is used as the reinforcement, and the upper and lower surfaces of the reinforcement are coated with modified asphalt rubber. The upper and lower surfaces of the modified asphalt layer are covered with polyethylene film, which is the waterproof membrane.
[0087] Example 2
[0088] First, mix 45 parts of 70# asphalt and 55 parts of high-grade waterproof asphalt and heat it to 175℃. Then add 10 parts of SBS and shear it at a speed of 3200r / min for 1.2 hours. Then add 15 parts of waste rubber powder and 12 parts of sepiolite powder and mix them. Continue shearing at this temperature and speed for 1 hour to obtain the modified asphalt coating.
[0089] The polyester felt is used as the reinforcement, and the upper and lower surfaces of the reinforcement are coated with modified asphalt rubber. The upper and lower surfaces of the modified asphalt layer are covered with polyethylene film, which is the waterproof membrane.
[0090] Example 3
[0091] First, mix 50 parts of 70# asphalt and 60 parts of high-grade waterproof asphalt, and heat it to 175℃. Then add 12 parts of SBS and shear it at a speed of 3200r / min for 1.2 hours. Then add 20 parts of waste rubber powder and 15 parts of sepiolite powder and continue shearing at the same temperature and speed for 1 hour to obtain the modified asphalt coating.
[0092] The polyester felt is used as the reinforcement, and the upper and lower surfaces of the reinforcement are coated with modified asphalt rubber. The upper and lower surfaces of the modified asphalt layer are covered with polyethylene film, which is the waterproof membrane.
[0093] Comparative Example 1
[0094] First, mix 50 parts of 70# asphalt and 60 parts of commercially available high-grade waterproof asphalt, heat it to 175°C, add 12 parts of SBS, and shear it at a speed of 3200r / min for 1.2 hours. Then add 20 parts of waste rubber powder and 15 parts of sepiolite powder, mix them, and continue shearing at the same temperature and speed for 1 hour to obtain the modified asphalt coating.
[0095] The polyester felt is used as the reinforcement, and the upper and lower surfaces of the reinforcement are coated with modified asphalt rubber. The upper and lower surfaces of the modified asphalt layer are covered with polyethylene film, which is the waterproof membrane.
[0096] Comparative Example 2
[0097] First, mix 50 parts of 70# asphalt and 60 parts of high-grade waterproof asphalt (Preparation Example 3), and heat to 175°C. Add 12 parts of SBS and shear at a speed of 3200r / min for 1.2h. Then add 20 parts of waste rubber powder and 15 parts of talcum powder and mix. Continue shearing at this temperature and speed for 1h to obtain the modified asphalt coating.
[0098] The polyester felt is used as the reinforcement, and the upper and lower surfaces of the reinforcement are coated with modified asphalt rubber. The upper and lower surfaces of the modified asphalt layer are covered with polyethylene film, which is the waterproof membrane.
[0099] Comparative Example 3
[0100] First, mix 50 parts of 70# asphalt and 60 parts of commercially available high-grade waterproof asphalt, heat it to 175°C, add 12 parts of SBS, and shear it at a speed of 3200r / min for 1.2 hours. Then, add 20 parts of waste rubber powder and 15 parts of talcum powder, mix them, and continue shearing at the same temperature and speed for 1 hour to obtain the modified asphalt coating.
[0101] The polyester felt is used as the reinforcement, and the upper and lower surfaces of the reinforcement are coated with modified asphalt rubber. The upper and lower surfaces of the modified asphalt layer are covered with polyethylene film, which is the waterproof membrane.
[0102] The properties of the waterproof membranes prepared in Examples 1-3 and Comparative Examples 1-3 were measured respectively.
[0103] Table 3 is Japan's six-level odor intensity classification table. Referring to Japan's six-level odor intensity classification method, the waterproof membranes prepared from the asphalt coating materials of Examples 1-3 and Comparative Examples 1-3 were evaluated for various properties. The evaluation results are shown in Table 4.
[0104] Table 3 Japanese odor intensity grades
[0105] strength index 0 Tasteless 1 Can barely smell 2 The smell is very weak but the properties can be distinguished 3 It is easy to sense the smell 4 strong smell 5 Unbearable strong smell
[0106] Table 4 Performance of waterproof membranes in Examples 1-3 and Comparative Examples 1-3
[0107]
[0108] The data in Table 4 above demonstrate that waterproof membranes prepared using the raw material system of the present invention not only exhibit excellent waterproofing properties, but also possess excellent low-temperature flexibility and heat resistance, and possess significant environmental advantages. When exposed to direct sunlight for one hour at an ambient temperature of 25°C, the surface temperature of the membranes prepared using this formulation is lower than that of conventional membranes. This demonstrates that the membranes can reduce surface temperature and aging under high-temperature conditions, effectively improving their aging resistance.
[0109] In summary, the waterproof membrane of the present invention can be applied to waterproofing and anti-seepage of industrial and civil building roofs, walls, kitchens and bathrooms, basements, swimming pools, as well as roads, bridges, subways, reservoirs and other projects, and is also applicable to the anti-corrosion protection of metal containers and pipelines.
[0110] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas. At the same time, for those skilled in the art, according to the ideas of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the contents of this specification should not be understood as limiting the present invention.
Claims
1. An aging-resistant SBS modified asphalt coating material, characterized in that: The coating material comprises the following raw materials in parts by weight: 40-50 parts by weight of 70# asphalt, 50-60 parts by weight of anti-aging high-grade waterproof asphalt, 8-12 parts by weight of SBS, 10-20 parts by weight of waste rubber powder, and 10-15 parts by weight of sepiolite powder; The high-grade waterproof asphalt includes the following raw materials: base asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler, adsorbent; The mass ratio of the matrix asphalt, catalytic oil slurry, furfural extracted oil, conversion agent, filler and adsorbent is 70-80:6-10:10-18:0.1-0.25:1-3:0.03-0.
05.
2. The aging-resistant SBS modified asphalt coating material according to claim 1 is characterized in that: The melt index of the SBS is 0.03-0.10 g / min; and / or, The particle size of the waste rubber powder is 60-80 mesh; and / or, The particle size of the sepiolite powder is 80-100 meshes.
3. The aging-resistant SBS modified asphalt coating material according to claim 1 or 2, characterized in that: In the high-grade waterproof asphalt, the furfural extracted oil includes one or a mixture of two of furfural extracted oil with three-line reduction and furfural extracted oil with four-line reduction; Preferably, the aromatic content in the furfural extracted oil is ≥40%.
4. The aging-resistant SBS modified asphalt coating according to any one of claims 1 to 3, characterized in that: In the high-grade waterproof asphalt, the adsorbent includes bamboo wood nanofiber aerogel; Preferably, the preparation method of the bamboo wood nanofiber aerogel comprises the steps of taking bamboo wood cellulose nanofibers and placing them in water and ethanol solutions for immersion, and the step of pressurizing and heating the nanofibers; Preferably, the impregnation step comprises the steps of adding water to the bamboo wood cellulose nanofibers for immersion for 20-30 hours, and then taking out the nanofibers and continuing to add ethanol solution for immersion for 20-30 hours; Preferably, the pressure and heat treatment step is performed for 6-10 hours.
5. The aging-resistant SBS modified asphalt coating according to any one of claims 1 to 4, characterized in that: In the high-grade waterproof asphalt, the filler includes activated palygorskite; Preferably, the method for preparing the activated palygorskite comprises the steps of adding the palygorskite to dilute hydrochloric acid and mixing, and treating the palygorskite at 50-80° C.; Preferably, the mass concentration of the dilute hydrochloric acid is 1%-2%; Preferably, the mass ratio of the palygorskite to the dilute hydrochloric acid is 1:2-4 g / mL; Preferably, the treatment time is 40-80 min; Preferably, the method further comprises the steps of washing and drying the treated activated palygorskite.
6. The aging-resistant SBS modified asphalt coating material according to any one of claims 1 to 5, characterized in that: The high-grade waterproof asphalt: The base asphalt includes heavy cross-linking 70# asphalt; and / or, The aromatic content of the catalytic cracking slurry is 40%-48%; and / or, The converting agent includes silicotungstic acid.
7. A method for preparing the aging-resistant SBS modified asphalt coating material according to any one of claims 1 to 6, characterized in that: The method comprises the steps of mixing selected amounts of the 70# asphalt, high-grade waterproof asphalt, SBS, waste rubber powder and sepiolite powder; Preferably, the temperature of the mixing step is 170-180°C; Preferably, the method further comprises the step of performing high-speed shearing at a rotation speed of 3000-3500 r / min for 1-1.5 h during the mixing process.
8. The method for preparing the aging-resistant SBS modified asphalt coating material according to claim 7, characterized in that: The method further comprises the step of preparing the high-grade waterproof asphalt, namely, the step of mixing selected amounts of the base asphalt, catalytic slurry, furfural extracted oil, conversion agent, absorbent and filler; Preferably, the temperature of the mixing step is 120°C-130°C.
9. An aging-resistant waterproof coiled material, characterized in that: It comprises a polyester felt reinforcement, wherein the upper and lower surfaces of the reinforcement are respectively provided with a modified asphalt rubber layer and a polyethylene film; The modified asphalt rubber layer is formed by the aging-resistant SBS modified asphalt coating material described in any one of claims 1-6.
10. A method for preparing the aging-resistant waterproof coiled material according to claim 9, characterized in that: The method comprises the steps of coating the anti-aging SBS modified asphalt coating material on the upper and lower surfaces of the polyester felt reinforcement respectively, and then covering the polyethylene film in turn.
Citation Information
Patent Citations
Coating and preparation method thereof as well as modified asphalt waterproof roll
CN109401344A
Medium-temperature modified asphalt mixture additive as well as preparation and use methods thereof
CN109988431A
Paligorskite composition modified asphalt and its manufacturing method
CN1730563A